Effect of Circuit Training on TNF Alpha Levels and Six Minutes Walk Test in Patients with Chronic Heart Failure - Fauzan Muttaqien; Sri Wahyudati; SefriNoventi Sofia; Sodiqur Rifqi (Fakultas Kedokteran Universitas Lambung Mangkurat, 2018)
Abstract: Physical exercise in patients with heart failure can decrease the level of proinflammatory biomarkers andincrease functional capacity. Circuit training is one of the most advantageous exercise models because it improves cardiorespiratory fitness and muscle strength.This study aimed to investigate the effect of circuit training on TNF alphaandsix minutes walk test in patients with chronic heart failure in RSUP Dr. Kariadi. Twenty-six stable chronic heart failure with reduced ejection fraction patients were randomized into exercise group that received circuit training in the rehabilitation center of Kariadi Hospital for a month and control group. TNF- α levels as a inflammatory biomarker and distance of six minute walk test as a functional capacity parameter were taken before and after the exercise period.Nine-teensubjects completed the study without any significant side effects.There was no significant difference in TNF-α levels before and after treatment between treatment groups and control groups (p=0,513). The treatment group with circuit training showed a greater increase in distance of six minute walk test than the control group (p=0,034).It was concluded that circuit training in patients with chronic heart failure can increase distance of six minute walk test, but no changes in TNF alpha levels. Keywords: Circuit training, TNF-a, six minute walk test